HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG STIMULASI PERKEMBANGAN DENGAN PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 1 – 5 TAHUN DI POSYANDU MEKARSARI NAYU TIMUR BANJARSARI - Ratna Indriati; Wiga Ami Widyanto; Anindya Dwi Pratiw (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstrakIntroduction: Under five years of age is an important period of growth and development. One aspect is the development of gross motor skills in children. Gross motor development are not optimal can lead to decreased creativity in adapting. One of the factors that influence the development of children is the stimulation of the parents. From the initial survey in posyandu Mekarsari obtained two (2 ) children aged 19 months and 26 months have not been able to walk on his own and from the interview, mothers do not understand about the stimulation of growth in children.The purpose: Of this study was to determine the relationship of the level of knowledge about stimulation of development with the development of gross motor in children aged 1-5 years in Posyandu Mekarsari Banjarsari.Method: Correlation research design with cross sectional approach. Subjects were 66 mother and their children aged 1 - 5 years in Posyandu Mekarsari with sampling technique by simple random sampling. Data were obtained by questionnaire to determine the level of knowledge about stimulation of development and DDST tests to determine the gross motor development in children. The data obtained were analyzed with chi-square test with p = 0.05 Results: Indicate the level of knowledge Capital on high category by 55 people (83.33%) and moderate categories 11 (16.67%), while children with gross motor development either as many as 47 children (71.21%) and unfavorable developments 19 children (28.79%). The results of the analysis using the chisquare test p = 0.005 obtained so that the value of p < 0.05, which means thatHo is rejected and Ha accepted.The Conclusion: Of the research was there is relationship of the knowledge about stimulation of development with the development of gross motor in children aged 1-5 years in posyandu Mekarsari.Keywords: Knowledge Level, stimulation of development, gross motor development